2000
DOI: 10.1002/lt.500060216
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A antibodies in liver transplant recipients: Evidence for loss of immunity posttransplantation

Abstract: Liver transplant recipients frequently have chronic liver diseases and should be considered for vaccination against hepatitis A virus (HAV). However, persistence of protective antibodies after orthotopic liver transplantation (OLT) has not been shown in this population, which may have implications for future vaccine recommendations. We evaluated the prevalence and epidemiological significance of immunoglobulin G (IgG) antibody to HAV (anti-HAV) in a nonvaccinated population before OLT (immunity from previous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Because of the acute nature of HAV infection, pretransplant testing is not routinely done, although hepatitis A vaccination of transplantation candidates is recommended ( 16 ). The multi–visceral organ recipient was vaccinated, but studies have shown loss of immunity to HAV after transplantation because of immunosuppression ( 19 , 20 ). The heart and kidney transplant recipients had evidence of immunity and probably were protected through previous vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the acute nature of HAV infection, pretransplant testing is not routinely done, although hepatitis A vaccination of transplantation candidates is recommended ( 16 ). The multi–visceral organ recipient was vaccinated, but studies have shown loss of immunity to HAV after transplantation because of immunosuppression ( 19 , 20 ). The heart and kidney transplant recipients had evidence of immunity and probably were protected through previous vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the seroprevalence in each geographic area may also affect the seroconversion rate after hepatitis A vaccination. In a previous study, 18% and 29% of the patients with positive pre-transplant anti-HAV had lost their immunity 1 and 2 years after transplant, respectively 16 . Therefore, post-transplant vaccination probably acts as a booster dose and yields a higher chance of seroconversion among these patients 26 .…”
Section: Discussionmentioning
confidence: 90%
“…According to the guidelines, hepatitis A vaccine should be given to either SOT candidates or recipients who have negative anti-HAV immunoglobulin G (IgG) 13,14 . However, there were scarce data on anti-HAV seroprevalence of standard 2-dose regimen in SOT and the results varied between countries [15][16][17] .…”
mentioning
confidence: 99%
“…This was reported in a retrospective study where 18% and 29% of patients with previously detectable anti-HAV IgG from natural infection became anti-HAV IgG non-detectable at 1 and 2 years post transplant. [13] Anti-HAV IgG antibody loss may be caused by strong anti-rejection regimens given following liver transplant (LT). These immune-suppressing medications, including high-dose systemic steroids and mycophenolate mofetil, may decimate some memory B-cell pools.…”
Section: Discussionmentioning
confidence: 99%